2015
DOI: 10.1210/jc.2014-4353
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Sugar Consumption May Be a Difficult Habit to Break: A View From the Brain and Body

Abstract: These experimental findings support a metabolic-brain-negative feedback pathway that is affected by sugar and may make some people under stress more hooked on sugar and possibly more vulnerable to obesity and its related conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(61 citation statements)
references
References 36 publications
(33 reference statements)
4
52
0
1
Order By: Relevance
“…Chronic stress may also lead to changes in food intake. Eating high sugar foods may be a coping mechanism to reduce stress, as it is shown that cortisol responses to a stress test may be attenuated on drinking sucrose-sweetened beverages 31. In addition, our findings imply that PED is similarly related to general and abdominal obesity, and that the strength of the associations is similar for BMI and WC.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Chronic stress may also lead to changes in food intake. Eating high sugar foods may be a coping mechanism to reduce stress, as it is shown that cortisol responses to a stress test may be attenuated on drinking sucrose-sweetened beverages 31. In addition, our findings imply that PED is similarly related to general and abdominal obesity, and that the strength of the associations is similar for BMI and WC.…”
Section: Discussionsupporting
confidence: 52%
“…This suggests that perceived discrimination might affect adiposity (eg, through hypercortisolism) across the whole body, rather than specific areas (eg, abdominal region). Increased fat and sugar intake due to chronic stress could also be equally related to increased BMI and WC 10 31…”
Section: Discussionmentioning
confidence: 99%
“…The Chinese study also revealed that non-drinkers were 1.3 times more likely to attempt suicide compared to those drinking such drinks less than once per day [13]. A recent experiment showed that sucrose beverage consumption lowered the salivary cortisol release induced by stress [20], which means that sugar beverages may function as a stress reliver. Thus, sugar's stress-relieving effects might be related to the lower likelihoods of suicide attempt in those with moderate carbonated beverage intake that were observed in our study.…”
Section: Discussionmentioning
confidence: 98%
“…For example, a recent study found that normoglycemic women randomized to consume high-sugar beverages over a 2-week period had a blunted cortisol response and reported less psychological distress to a laboratory stressor as compared with women randomized to consume aspartame-sweetened beverages, suggesting a negative feedback loop between glucose consumption and stress reactivity. 22 Consistent with this, individuals with type 2 diabetes have reduced glucocorticoid responsivity to laboratory stressors relative to normoglycemic individuals. 23 These stress-coping behaviors appear to be conserved.…”
Section: Diabetes Disparities In Contextmentioning
confidence: 66%